Social Self‐Sorting of Colloidal Families in Co‐Assembling Microgel Systems. Issue 8 (18th January 2017) - Han, Kang; Go, Dennis; Tigges, Thomas; Rahimi, Khosrow; Kuehne, Alexander J. C.; Walther, Andreas
Abstract: Colloids are valuable model systems to understand the structure and dynamics of matter, explore new self‐assembly concepts, and realize advanced materials. Herein, we demonstrate social self‐sorting of co‐assembled families of colloids by orthogonal host/guest recognition using cyclodextrins. We show that mixtures of four partners self‐sort into their respective families without mutual interference. Additionally, the self‐assemblies and their interactions are switchable using orthogonal triggers. This study goes beyond previous features of molecular self‐sorting, and opens the design space for future self‐sorting colloidal systems via rationally designed molecular recognition. Abstract : Finding their partners : In multicomponent systems, colloids bearing molecular recognition units can self‐sort in a social manner into their respective families. Additionally, the self‐assemblies and their interactions are switchable using orthogonal triggers, such as light and redox chemistry.